The Influence of Leadership and Work Culture on Organizational Commitment and Its Impact on Employee Performance at Rupbasan All Riau Region - Norawati, Suarni; Diharja, Muhammad; Basem, Zamhir (Dinasti Publisher, 2024)
High employee performance is always a demand for organizational leaders, both public organizations and private organizations, because high employee performance will have an impact on the development of the organization in the future. Therefore, knowing the factors that influence employee performance is an important thing to do. This research was conducted in Rupbasan throughout the Riau Region with the research aim of knowing and analyzing the influence of leadership and work culture on organizational commitment, knowing and analyzing the direct influence of leadership and work culture on employee performance, knowing and analyzing the influence of organizational commitment on employee performance, knowing and analyze the indirect influence of leadership and work culture on performance through organizational commitment. This research uses primary data and secondary data obtained by distributing questionnaires and conducting research files. The sample for this research consisted of 61 Rupbasan employees throughout the Riau Region. Data analysis and hypothesis testing tools are used Structural Equation Modling using the SmartPLS program. Hypothesis testing is carried out at alpha 5%. Based on the research results, it was concluded that leadership and work culture were proven to have a significant influence on organizational commitment, leadership was directly proven to have a significant influence on employee performance, work culture was not directly proven to have a significant influence on employee performance, organizational commitment was proven to have a significant influence on employee performance, leadership and Work culture has been proven to have a significant influence on performance through organizational commitment, or organizational commitment can mediate the influence of leadership and work culture on employee performance